Vocabulary learning strategies :a survey among academic reading and writing and preparatory english (one) undergraduates of UNIMAS - Nur Syazwani, Mohd Yusoff. (UNIMAS, 2009)
This study aims to investigate vocabulary learning strategies among Academic Reading and Writing and Preparatory English One of Unimas. It also aims to find out the frequent vocabulary learning strategies applied by undergraduates enrolling Academic Reading and Writing and Preparatory English One course. This study also attempts to look at similarities vocabulary learning strategies used by different level of students particularly Band one to three achievers of both courses.Finally it will looks at similarities in the frequency of the use of vocabulary learning strategies between male and female undergraduates. Questionnaires adapted from Catalan (2003) were used to gather the data and was analyzed using SPSS version 13.The findings revealed that the undergraduates of both groups used variety of vocabulary learning strategies. The result also showed that Band one to Band three achievers of taking both courses used similar strategies in learning vocabulary. Male and female involved in this used the similar vocabulary learning strategies.